Pengaruh Senam Aerobik terhadap Kebugaran Jasmani, Komposisi Tubuh, dan Kualitas Tidur Mahasiswa Universitas PGRI Mahadewa Indonesia - Ni Luh Putu Indrawathi; I Putu Astrawan; Komang Ayu Tri Widhiyanti; I Putu Eri Kresnayadi; Ni Luh Gde Widiantari (MAN Insan Cendekia Jambi, 2026)
Aerobic exercise is a structured physical activity with great potential to enhance students' fitness and well-being. This study aimed to examine the effects of an aerobic exercise program on physical fitness, body composition, and sleep quality among students of Universitas PGRI Mahadewa Indonesia. A quasi-experimental design with a pretest-posttest control group was employed. Seventy-two second-semester female students were selected through purposive sampling and randomly assigned to an experimental group (n=36) participating in a moderate-intensity aerobic exercise program for 10 weeks (3 sessions/week, 60 minutes/session), and a control group (n=36) receiving no additional treatment. Physical fitness was assessed using the modified Indonesian Physical Fitness Test (TKJI) and VO₂max (Rockport Walking Test); body composition was measured via bioelectrical impedance analysis (BIA); sleep quality was evaluated using the Indonesian version of the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using paired t-test, independent t-test, and ANCOVA at α=0.05. Results demonstrated significant improvements in VO₂max (p=0.000; Δ=4.31 mL/kg/min), reduction in body fat percentage (p=0.000; Δ=-2.87%), increase in muscle mass (p=0.002; Δ=+1.24 kg), and improvement in PSQI scores (p=0.000; Δ=-2.6 points) in the experimental group compared to controls. It is concluded that a structured 10-week aerobic exercise program significantly improves physical fitness, body composition, and sleep quality of female students at UPMI. These findings support integrating aerobic exercise as a mandatory component in college student wellness programs.